Низькотемпературнi електроннi спектри домiшок у кристалах нафталiну - Curmei, N. D.; Klishevich, G. V.; Melnyk, V. I. (Publishing house "Academperiodika", 2018)
This work relates to the study of vibrational structures in the electron spectra of naphthalene crystals with impurities of b- and a-naphthalene fluorine with concentrations of 10^−4 to 10 wt.% at a temperature at 4.2 K. It is determined that, at low impurity concentrations, the spectra have a doublet structure and consist of narrow quasilines with initial values of v01 = 31322 cm^−1 and v02 = 31226 cm^−1, which are resonance-coincident in the absorption and fluorescence spectra. It is demonstrated that if the impurity concentration increases, the series of narrow quasilines appear in the areas of the 0-0 transitions of the impurity centers of both types together with the doublet structure. A part of these quasilines is polarized predominantly along the b-axis of a naphthalene crystal. The model is proposed for impurity centers, which induce the generation of new spectral bands. This model is based on the interaction of translation-nonequivalent impurity molecules in the elementary lattice cell of a naphthalene crystal. At high impurity concentrations, the resonance-symmetric wide spectral bands appear in the absorption and fluorescence spectra. The analysis of the results obtained is performed with consideration for the Franck–Condon interaction and the Herzberg–Teller interaction.